Revision of the West-Palaearctic species of the tribe Cerioidini (Diptera, Syrphidae) - Steenis, Jeroen Van; Ricarte, Antonio; Vujić, Ante; Birtele, Daniele; Speight, Martin C. D. (Zootaxa, 2016)
The West-Palaearctic cerioidines (Syrphidae: Cerioidini) are revised, including species of the genera Ceriana Rafinesque, Primocerioides Shannon, and Sphiximorpha Rondani. Three new species are described, Ceriana glaebosa van Steenis & Ricarte sp. n. (Cyprus), Ceriana media van Steenis & Ricarte sp. n. (Afghanistan and Iran) and Ceriana skevingtoni van Steenis & Ricarte sp. n. (Armenia, Azerbaijan and Iran). The following names are proposed as junior synonyms: Cerioides caucasicus Paramonov, 1927 [= Ceriana conopsoides (Linnaeus, 1758)], Ceria binominata Verrall, 1901 [= Sphiximorpha garibaldii (Rondani, 1860)], Ceriana worelli, Brădescu, 1972b [= Sphiximorpha garibaldii (Rondani, 1860)] and Sphiximorpha hiemalis Ricarte, Nedeljković & Hancock, 2012 [= Primocerioides regale Violovitsh, 1985]. Identification keys, biological data and distribution maps for the studied taxa are provided. Conops vaginicornis Schrank, 1803 is discarded as a synonym of Ceriana conopsoides and should be considered as nomen dubium.